ä½¿ç”¨å¡ç‰‡æé«˜è¿¦å—å¦æ ¡åˆä¸ä¸‰å¹´çº§å¦ç”Ÿäººè¯»æ±‰å—èƒ½åŠ› - Harfina, Harfina; Thamrin, Lily; Kiong, Bun Yan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract  Card media is an interesting tool to be implemted in teacing and learning process. In order to get the students understand the subject well,it is good to implement the card media, beside it is efficient in terms if time management yet it enchances student?s ability in under standing the subject well,especially in reading chinese character.The purpose of the implementation of card media is to see well student?s ability enchanced or not by observasing their respond when card media is being used. To see the effect of card media, the writer decide to do the research in third grade of SMP Kristen Kanaan, the result was it significantly enchanced the student?s ability in reading chinese characters, it can be seen from their final score. The percentage of pre-test score was 38.13%, and after the writer done the research, the percentage of the final score post-test increased uo to 74,58%, it shows that card media was successfully enchanced the student?s ability in reading chinese character.              Key words : chinese character, reading, card media